"I…don't want to see you flashing your bits around": Exhibitionism, othering and good motherhood in perceptions of public breastfeeding. (May 2016) - Grant, Aimee
Abstract: Stigma and concern about public breastfeeding have been identified as contributing towards low breastfeeding rates in high-income countries. Despite this, very little research has examined public perceptions of breastfeeding. Among existing studies, lack of familiarity with breastfeeding, sexist views and hyper-sexualisation of the breast were identified alongside discomfort at viewing breastfeeding by strangers. During 2014, in the United Kingdom (UK), several cases of women being criticised for breastfeeding in public appeared in national newspapers. A Critical Discourse Analysis approach was used to theoretically frame analysis of 884 naturally occurring comments relating to a protest supporting women's right to breastfeed in public from the UK's most popular online news site, Mail Online. Findings are discussed in relation to mothers' roles as citizens and sexual beings, with a particular focus on the visibility of breasts in public space. Women who breastfeed in public were viewed as unattractive, lazy, bad parents and lacking in self-respect. More specifically, women who breastfed in public were viewed as exhibitionist. This was contrasted with the desirability of breastfeeding within the home, which was seen as an appropriate way to feed an infant. The undesirability of public breastfeeding was inherently linked to sexuality, with breastfeeding women viewed as sexual aggressors ("flashers") or inviting sexual contact from men. It is argued that these views originate in unequal gender relationships in society and the framing of breasts as sexual rather than nurturing. These discourses are played out in public space in which mothers are marginalised in a patriarchal society.